AI Battle Royale How to Protect Your Job from Disruption in the 4th Industrial Revolution - Recanati, Ashley Marc. (Cham : Springer International Publishing : Imprint: Springer, 2023)
AI, Big Data and other 4th industrial revolution technologies are poised to wreak havoc in virtually every industry, unlocking huge productivity gains via automation of labor both manual and cognitive. Less discussed are the impacts on workers, who see the value of their skills erode, along with the menace of mass structural unemployment. How can workers assess their vulnerabilities? What can they do to improve their prospects, effective immediately? In this book, you will learn how to: - Survey new tech and decrypt their potential impacts on work - Assess your strengths and weaknesses in the face of AI, the shared economy, and other tech-propelled threats - Foment a battle plan to survive and thrive Ashley Recanati provides guidance for employees to rise above their peers and preserve their value, in a book that will interest managers and scholars, but foremost destined to ordinary workers.
Part I: Context -- Chapter 1: Possible Futures -- Chapter 2: Past Industrial Revolutions -- Chapter 3: Tech -- Part 2: Work -- Chapter 3: Sectorial and Corporate Disruption -- Chapter 2: Job Disruption -- Chapter 3 : Tasks -- Chapter 4 : Other Aspects -- Conclusion.
Keywords: Business information services; Management; Personnel management; IT in Business; Management; Human Resource Management